Pengaruh Pengaruh Metode Game Based Learning (GBL) Berbantuan Apilaksi Wordwall Terhadap Keterampilan Menulis Permulaan Siswa Kelas 1 SDN 04 Terandam - Iqmal Desrial; Annisa Kharisma; Sry Apfani (LP2M Universitas Adzkia, 2025)
This study was motivated by the low beginning writing skills of first-grade students at SDN 04 Terandam, which were still below the minimum learning achievement criteria. This condition was caused by less varied teaching methods and students’ lack of attention and focus during the learning process. The study aimed to determine the significant effect of the Game Based Learning (GBL) method assisted by the Wordwall application on students’ beginning writing skills. This research used a quasi-experimental method with a posttest-only design. The population consisted of 30 first-grade students, with class IB as the experimental group and class IA as the control group using saturated sampling. Data were collected through a beginning writing skills test and analyzed using a t-test. The results showed that the experimental class achieved a higher average score than the control class, namely 82.67 and 77. The hypothesis test results indicated that tcount > ttable (1.722 > 1.701), meaning that the use of the GBL method assisted by Wordwall had a significant effect on students’ beginning writing skills.